Genome Editing for Sustainable Agriculture in Africa - Tripathi, Leena; Dhugga, Kanwarpal S.; Ntui, Valentine O.; Runo, Steven; Syombua, Easter D.; Muiruri, Samwel; Wen, Zhengyu; Tripathi, Jaindra N. (Frontiers in Genome Editing, 2022)
Sustainable intensification of agriculture in Africa is essential for accomplishing food and nutritional security and addressing the rising concerns of climate change. There is an urgent need to close the yield gap in staple crops and enhance food production to feed the growing population. In order to meet the increasing demand for food, more efficient approaches to produce food are needed. All the tools available in the toolbox, including modern biotechnology and traditional, need to be applied for crop improvement. The full potential of new breeding tools such as genome editing needs to be exploited in addition to conventional technologies. Clustered regularly interspaced short palindromic repeats/CRISPR-associated protein (CRISPR/Cas)-based genome editing has rapidly become the most prevalent genetic engineering approach for developing improved crop varieties because of its simplicity, efficiency, specificity, and easy to use. Genome editing improves crop variety by modifying its endogenous genome free of any foreign gene. Hence, genome-edited crops with no foreign gene integration are not regulated as genetically modified organisms (GMOs) in several countries. Researchers are using CRISPR/Cas-based genome editing for improving African staple crops for biotic and abiotic stress resistance and improved nutritional quality. Many products, such as disease-resistant banana, maize resistant to lethal necrosis, and sorghum resistant to the parasitic plant Striga and enhanced quality, are under development for African farmers. There is a need for creating an enabling environment in Africa with science-based regulatory guidelines for the release and adoption of the products developed using CRISPR/Cas9-mediated genome editing. Some progress has been made in this regard. Nigeria and Kenya have recently published the national biosafety guidelines for the regulation of gene editing. This article summarizes recent advances in developments of tools, potential applications of genome editing for improving staple crops, and regulatory policy in Africa.